Low-temperature semi-solid-state H2 battery with high energy density - Xiuquan Chen; Yuhua Zhao; Simin Hong; Xiaodong Rang; Hong Dong; Jie Zhang; Shangjun Lu; Xiang Cui; Yajing Liu (Chemical Engineering Journal, 2026)

NPR1 modulates DNA replication in vascular endothelial cells via the transcription factor E2F2 - Fengqing Zhang; Hong Tang; Xiaocheng Mao; Simin Xiong; Yiqi Wan; Wei Yuan; Hongfei Liu (Genes & Genomics, 2025)

Antitumor activity of evodiamine analogs by targeting PKCβI in gemcitabine-resistant pancreatic cancer cells - Eun Seo Bae; Junhwa Hong; Yijae Lim; Woong Sub Byun; Simin Chun; Suckchang Hong; Sang Kook Lee (Phytochemistry Letters, 2025)

Corrigendum to “Investigation of the formation mechanism and β-carotene encapsulation stability of emulsion gels based on egg yolk granules and sodium alginate” [Food Chem. 400 (2023) 134032] - Hong Zhang; Simin Tan; Hongmei Gan; Huajiang Zhang; Ning Xia; Longwei Jiang; Haowei Ren; Xiaonan Zhang (Food Chemistry, 2025)

Numerical study on the stability of offshore pile-soil systems considering pore pressure response induced by extreme storms - Simin Xu; Xiaolei Liu; Cheng Zhang; Hong Zhang; Botao Xie; Xingsen Guo (Ocean Engineering, 2025)

Spectroscopic method to study the effect of lightning return stroke channel expansion on atmospheric pressure - Jin Qin; Simin Xue; Ping Yuan; Zijiang Liu; Hua Yuan Shi; Tingting An; Hong Deng; Yingying An (Atmospheric Research, 2024)

Numerical Investigation into the Stability of Offshore Wind Power Piles Subjected to Lateral Loads in Extreme Environments - Miaojun Sun; Zhigang Shan; Wei Wang; Simin Xu; Xiaolei Liu; Hong Zhang; Xingsen Guo (Journal of Marine Science and Engineering, 2024)
Monopile foundations are extensively utilized in the rapidly expanding offshore wind power industry, and the stability of these foundations has become a crucial factor for ensuring the safety of offshore wind power projects. Such foundations are subjected to a myriad of complex environmental loads during their operational lifespan. Whilst current research predominantly concentrates on the effects of wind, wave, and current loads on monopile stability in extreme environments, it is imperative to consider the potential influence of unexpected submarine landslide loads. In this study, we provide a comprehensive overview of wind, wave, current, and submarine landslide loads on monopile foundations in extreme environments. Subsequently, we establish a finite element model for analyzing the stability of monopiles under complex lateral loads, and validate the accuracy of the model by comparing it with the previous numerical findings. A case study is performed with reference to the Xiangshui Wind Farm project to analyze the effects of varying submarine landslide densities, velocities, impact heights, and seabed sediment strengths on pile head horizontal displacement, pile rotation at the mudline, and maximum bending moment. The findings indicate that the increase in submarine landslide density, velocity, and impact height leads to an increase in horizontal displacement at the pile head, pile rotation at the mudline, and maximum bending moments, and a horizontal failure mode is observed in seabed sediments. Furthermore, under the same load conditions, a decrease in seabed sediment strength and internal friction angle triggers instability in monopiles, with a noteworthy transition from horizontal failure to deep-seated seabed sediment failure. Finally, we propose a criterion for monopile instability under diverse loading conditions.

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Investigation of the formation mechanism and β-carotene encapsulation stability of emulsion gels based on egg yolk granules and sodium alginate - Hong Zhang; Simin Tan; Hongmei Gan; Huajiang Zhang; Ning Xia; Longwei Jiang; Haowei Ren; Xiaonan Zhang (Food Chemistry, 2023)

Gene expression profiles in the brain of phenylketonuria mouse model reversed by the low phenylalanine diet therapy - Sha Hong; Tianwen Zhu; Simin Zheng; Xia Zhan; Feng Xu; Xuefan Gu; Lili Liang (Metabolic Brain Disease, 2021)